Mesenchymal stromal cell-derived small extracellular vesicles restore lung architecture and improve exercise capacity in a model of neonatal hyperoxia-induced lung injury. Issue 1 (1st January 2020) - Willis, Gareth R.; Fernandez-Gonzalez, Angeles; Reis, Monica; Yeung, Vincent; Liu, Xianlan; Ericsson, Maria; Andrews, Nick A.; Mitsialis, S. Alex; Kourembanas, Stella
ABSTRACT: Early administration of mesenchymal stromal cell (MSC)-derived small extracellular vesicles (MEx) has shown considerable promise in experimental models of bronchopulmonary dysplasia (BPD). However, the ability of MEx to reverse the long-term pulmonary complications associated with established BPD remains unknown. In this study, MEx were isolated from media conditioned by human Wharton's Jelly-derived MSC cultures. Newborn mice (FVB strain) were exposed to hyperoxia (HYRX (75% O2)) before returning to room air at postnatal day 14 (PN14). Following prolonged HYRX-exposure, animals received a single MEx dose at PN18 or serial MEx treatments at PN18-39 ("late" intervention). This group was compared to animals that received an early single MEx dose at PN4 ("early" intervention). Animals were harvested at PN28 or 60 for assessment of pulmonary parameters. We found that early and late MEx interventions effectively ameliorated core features of HYRX-induced neonatal lung injury, improving alveolar simplification, pulmonary fibrosis, vascular remodelling and blood vessel loss. Exercise capacity testing and assessment of pulmonary hypertension (PH) showed functional improvements following both early and late MEx interventions. In conclusion, delivery of MEx following prolonged HYRX-exposure improves core features of experimental BPD, restoring lung architecture, decreasing pulmonary fibrosis and vascular muscularization, ameliorating PH and improving exercise capacity. Taken together, delivery of MEx may not only be effective in the immediate neonatal period to prevent the development of BPD but may provide beneficial effects for the management and potentially the reversal of cardiorespiratory complications in infants and children with established BPD.